Digital Photography: a Tool for Nursing on the Assessment of Pressure Lesions - Olga L. Cortés; Paula A. Alvarado; Yudy A. Rojas; Luz Dary Salazar; Ximena Acuña; Maribel Esparza (Universidad de Antioquia, 2018)
Objective. This work sought to assess the inter-observer agreement among expert nurses by using digital photographs and between these experts and the nursing registries in the electronic clinical record in the identification and degree of PL. Methods. This was an observational study, including 225 photographic records (184 patients, 97 with pressure lesion and 128 registries without lesion) randomly selected from the total of photographs registered in the PENFUP clinical trial (without lesion). Three expert evaluators assessed said photographs in masked manner. The notes from nursing of patients included related with the description of PL were evaluated. The Kappa index was calculated along with the composite agreement ratio for each evaluation. Results. Good agreement was observed among expert evaluators of photographic records on the presence of PL and between good-moderate for the degree of PL (I-II). Likewise, upon evaluating the agreement between the nursing registries of PL and the photographic assessment of the three expert evaluators of the same areas, good agreement was observed to determine the presence of PL and moderate agreement for the degrees of PL. Conclusion. Photographic records are a tool that permits recognizing the types of wounds, as well as the visualization of the different layers of skin injured. The study highlights the importance of assessment and validation by experts, given that it permits identifying existing problems that can lead to the underestimation or overestimation of PL when conducted by a single caregiver.   How to cite this article: Cortés OL, Alvarado PA, Rojas YA, Salazar LD, Acuña X. Digital Photography: a Tool for Nursing on the Assessment of Pressure Lesions. Invest. Educ. Enferm. 2018; 36(2):e07.